Totally Laparoscopic Gastrectomy for Gastric Cancer Associated with Recklinghausen's Disease. (6th June 2010) - Sakaguchi, Yoshihisa; Ikeda, Osamu; Ohgaki, Kippei; Oki, Eiji; Chinen, Yoshiki; Sakamoto, Yasuo; Minami, Kazuhito; Toh, Yasushi; Okamura, Takeshi
Abstract : This paper documents the first case of gastric cancer associated with Recklinghausen's disease, which was successfully treated by a totally laparoscopic operation. A 67-year-old woman with Recklinghausen's disease was referred to this department to undergo surgical treatment for early gastric cancer. The physical examination showed multiple cutaneous neurofibromas throughout the body surface, which made an upper abdominal incision impossible. Laparoscopic surgery requiring only small incisions was well indicated, and a totally laparoscopic distal gastrectomy with lymph node dissection was performed. Billroth I reconstruction was done intra-abdominally using a delta-shaped anastomosis. The patient followed a satisfactory postoperative course with no complications. Since the totally laparoscopic gastrectomy has many advantages over open surgery, it should therefore be preferentially used as a less invasive treatment in the field of gastric cancer.